2016
DOI: 10.1515/rjim-2016-0027
|View full text |Cite
|
Sign up to set email alerts
|

Cinacalcet versus Parathyroidectomy in the Treatment of Secondary Hyperparathyroidism Post Renal Transplantation

Abstract: Background. Persistent hyperparathyroidism (HPT) with hypercalcemia is prevalent after transplant and is considered a risk factor for progressive bone loss and fractures and vascular calcification, as well as the development of tubulointerstitial calcifications of renal allografts and graft dysfunction. The subtotal parathyroidectomy is the standard treatment, although currently it has been replaced by the calcimimetic cinacalcet.Aim. The hypothesis of this study is that subtotal parathyroidectomy is superior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…Furthermore, as a calcimimetic, cinacalcet activates calcium-sensitive receptors of the parathyroid (30). Certain studies have suggested that cinacalcet is able to significantly inhibit PTH secretion so as to reduce the number of parathyroidectomy operations (31,32). With the application of cinacalcet, the present analysis indicated that there was a significant decreasing trend of serum calcium.…”
Section: Discussionmentioning
confidence: 50%
“…Furthermore, as a calcimimetic, cinacalcet activates calcium-sensitive receptors of the parathyroid (30). Certain studies have suggested that cinacalcet is able to significantly inhibit PTH secretion so as to reduce the number of parathyroidectomy operations (31,32). With the application of cinacalcet, the present analysis indicated that there was a significant decreasing trend of serum calcium.…”
Section: Discussionmentioning
confidence: 50%
“…In a study on 59 kid-ney transplant recipients with hyperparathyroidism, parathyroidectomy was compared with cinacalcet by changes in calcium and phosphorus and iPTH. The study demonstrated that correction of severe hyperparathyroidism was similar in both surgical and cinacalcet groups [5]. The effect of cinacalcet was shown in a CKD patient with secondary hyperparathyroidism despite subtotal parathyroidectomy [6].…”
Section: Discussionmentioning
confidence: 87%
“…Parathyroidectomy has been suggested by others as a harmless process (19) and in long-term there was no significant difference between them and cinacalcet using group (20). There is also an interesting report of rigorous bone loss with persistent HPT in a kidney recipient efficiently managed by Denosumab and vitamin D combination (21).…”
Section: Managementmentioning
confidence: 97%